Antioxidant, anti-inflammatory and antidiabetic activities of the combination of Curcuma longa (Zingiberaceae), Aframomum melegueta (Zingiberaceae) and Piper guineensis (Piperaceae) compared to plants alone - Blanchard M. Mayele; Clément M. Mbadiko; Armandine Mubwele; Gustave I. Nyamangombe; Nadège N. Kabamba; Koto-Te-Nyiwa Ngbolua; Théophile F. Mbemba (Orapuh Journal)
Introduction